Custom Sanctions for Sanctions on Same Marriage in Petalangan Malay Community Viewed from Islamic Law - M Rivaldo; Desi Apriani; Selvi Harvia Santri; Rosyidi Hamzah; Syafrinaldi Syafrinaldi; Heni Susanti; Irwanto Irwanto (Proceeding International Conference on Malay Identity, 2021)
Abstract Same-tribal marriages are common nowadays, because men and women love each other. However, this research focuses on the customary sanctions for same-ethnic marriages carried out by the Petalangan Malay indigenous people. Same-tribal marriage in Islam has no rules, but in customary law, same-tribal marriage will result in the consequences of customary law that applies in the Petalangan Malay indigenous people. Based on the background of the problem, the formulation of the problem raised is, what is the history of the Prohibition of Same-ethnic Marriage in the Petalangan Malay Indigenous Community in the Perbatinan Bunut Region. The research method is sociological law which is research that goes directly to the field. This research was conducted in the Balam Merah Spiritual Area, Pelalawan Regency. From this research, it is known that historically the prohibition on same-ethnic marriages for ninik mamak testifies that one person or one ethnic group is brother and sister. Therefore, if a person or group of people is prohibited from marrying, the prohibition is highly trusted and if it is carried out, bad things will happen to the couple and they are afraid of sanctions